How Can L2 Lexicon Be Proceduralized While Interacting with Proceduralized L2 Grammar: A Cognitively Linguistic Model of the Declarative/Procedural Interface: A Cognitively Linguistic Model. - Khresheh, Asim Mohammad (JOURNAL OF ADVANCES IN LINGUISTICS, 2018)
This article sheds light on how L2 lexicon should be considered cognitive and thus recalled for L2 grammar and how the latter embraces L2 lexicon due to its meaningfulness derived from L1. In so doing, this review article shows a possible interaction of the proceduralized knowledge of L2 grammar with the declarative knowledge of L2 lexicon from a cognitively linguistic perspective. This results in getting L2 lexicon proceduralized so as to support the weak interface position, i.e. partial conversion of declarative knowledge into proceduralized one. However, this article does not support the strong interface position, i.e. total conversion of declarative knowledge into proceduralized one as declarative language irregularities are not cognizable as declarative meaningful lexicon. Although there has been a debate whether learnt/declarative knowledge can be converted into acquired/proceduralized knowledge, cognitively linguistic consideration has been taken so far to support this transfer of knowledge. That is why; this article views how cognizable L2 vocabularies are to be recruited by L2 proceduralized grammar.